Women's law‐making and contestations of "marriage" in African conflict situations. Issue 4 (6th December 2021) - Bunting, Annie; Tasker, Heather; Lockhart, Emily
Abstract: International criminal law has developed significantly over the past 20 years since the establishment of the ad hoc Tribunals and International Criminal Court. Much scholarly attention has focused on the politics and jurisprudence of these courts, with particular focus on the prosecution of sexual and gender‐based violence. This article adds to the literature with comparative, qualitative research with survivors of conflict‐related forced marriage in Liberia, Sierra Leone, and Uganda, revealing context‐specific understandings of marriage, consent and harm. We argue women exercise "tactic agency" in captivity in ways that are, taken together, "law‐making" in their contestations over the socio‐legal categories of marriage. Their contestations of marriage impact the norms within rebel groups as well as the development of new crimes against humanity in international criminal law. Building on the empirical findings, we argue that prosecution of crimes against humanity and reparation programs ought to be flexible and responsive enough to capture the varied experiences of women and girls abducted in war for purposes of sexual exploitation.